Badanie Wpływu Efektu Bauschingera na Plastyczne Przystosowanie się do Konstrukcji (Na Przykładzie Układu Prętowego) - Kowalczyk, K.; Życzkowski, M. (Engineering Transactions, 1974)
The strain bardening hypothesis assumed exerts a certain influence on the shakedown of the structure. In the present paper the problem is reduced to an analysis of the influence of the Bauschinger effect on the shakedown process. The considerations concern an example of a rod subject to cyclic axial load (Fig. 1), a general hypothesis of combined strain hardening, with an arbitrary but fixed contribution of the Bauschinger effect, (2.11) and (2.12). The analysis was performed by the "step by step" method for the consecutive semicycles of loading. The residual stress was determined as the stress corresponding to certain selected loading cycles (control cycles). The results were illustrated on the plane of stresses and in the space of parameters p=f(1, ß), where p. dimensionless load, l dimensionless strain hardening parameter of the material, ß coefficient of contribution of the Bauschinger effect. Decreasing the contribution of the Bauschinger effect increases the domain of plastic shakedown of the structure; a similar remark applies to the decrease of 1.